Meningioma with Hyperostosis: A Clinical Review up to Acrylic Cranioplasty Reconstruction in 3 Cases - Tohari, Khamim; Siahaan, Salmon Charles; Dzaky, Rafi Daffa; Arisanti, Raden Roro Shinta; Adam, Kamila (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Meningioma is a type of tumor that commonly occurs in the central nervous system (CNS). Hyperostosis can occur in meningiomas. Hyperostosis is a condition in which the bone surrounding a meningioma thickens abnormally. Although hyperostosis is usually benign, leaving a small portion of bone that still has hyperostosis can increase the risk of recurrence. The case report was carried out by reviewing 3 medical records of meningioma sufferers with hyperostosis.